2020
DOI: 10.1101/2020.03.27.011437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complimentary action of structured and unstructured domains of epsin supports clathrin-mediated endocytosis at high tension

Abstract: Membrane tension plays an inhibitory role in clathrin-mediated endocytosis (CME) by impeding the transition of flat plasma membrane to hemispherical clathrin-coated structures (CCSs). Membrane tension also impedes the transition of hemispherical domes to omegashaped CCSs, a necessary step before their internalization via dynamin-mediated membrane scission. However, CME is not completely halted in cells under high tension conditions. Here we find that epsin, a membrane bending protein which inserts its N-termin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…This organization is similar to that of the homologous nucleation promoting factor Las17 in budding yeast (Mund et al, 2018). Filaments nucleated at the base of CCPs would be able to interact with coat proteins such as Hip1R and Epsin1/2/3 to generate forces to invaginate the plasma membrane (Hassinger et al, 2017;Mund et al, 2018;Akamatsu et al, 2020;Joseph et al, 2020). Intriguingly, we also sometimes observed a strikingly different N-WASP spatial organization in which it was distributed over the full clathrin coat.…”
Section: N-wasp Spatial Organization Suggests An Actin Force Generation Control Mechanismsupporting
confidence: 61%
“…This organization is similar to that of the homologous nucleation promoting factor Las17 in budding yeast (Mund et al, 2018). Filaments nucleated at the base of CCPs would be able to interact with coat proteins such as Hip1R and Epsin1/2/3 to generate forces to invaginate the plasma membrane (Hassinger et al, 2017;Mund et al, 2018;Akamatsu et al, 2020;Joseph et al, 2020). Intriguingly, we also sometimes observed a strikingly different N-WASP spatial organization in which it was distributed over the full clathrin coat.…”
Section: N-wasp Spatial Organization Suggests An Actin Force Generation Control Mechanismsupporting
confidence: 61%
“…Additionally, Caveolin-1 redistributes to the upstream edge of ECs subjected to HSS [67]. Thus, HSS might lead to a translocation of Caveolin-1 to areas of high mechanical tension which impedes internalization via CvME [68]. In support of this, it was observed that an increase in membrane tension, induced by mechanical stress, leads to rapid disassembly of caveolae in human cells [69].…”
Section: Discussionmentioning
confidence: 99%
“…In these acquisitions, the total internal reflection of the excitation beam creates an evanescent field that illuminates the lateral regions of CPs at a higher intensity compared to the apex, which is further away from the glass substrate. As a result, formation of CPs is marked by a characteristic "ring" pattern (100-200 nm in diameter) under super-resolution imaging (Li et al, 2015;Joseph et al, 2020;Willy et al, 2021b) (Figures 1A,B). Reducing the excitation NA (i.e., incidence angle of the excitation beam) enables increasing the penetration depth of the illumination field, i.e., approaching the structured illumination microscopy at the grazing incidence mode (GI-SIM), and imaging deeper inside cultured cells and fruit fly embryos with enhanced spatiotemporal resolution (Guo et al, 2018).…”
Section: Formation and Internalization Of Canonical Clathrin-coated P...mentioning
confidence: 99%
“…Increased membrane tension reduces the initiation density (Ferguson et al, 2017), and slows down the growth and dissolution rates of endocytic clathrin-coated structures (Ferguson et al, 2016). Moreover, internalization of CPs from the plasma membrane becomes dependent on the curvature generating adaptor proteins (Joseph et al, 2020;Willy et al, 2021a) and the forces provided by actin polymerization under increased tension (Boulant et al, 2011;Jin et al, 2022;Kaplan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%